Dermo traction as a solution to major skin defects: a prospective study in a tertiary care hospital of South Odisha - Sahu, Anil K.; Panda, Chandan K. (International Journal of Research in Orthopaedics, 2019)
Background: Soft tissue loss with exposure of underlying tissue is a challenge to all Orthopedics surgeons. The present prospective study described dermo-traction technique using infant feeding tube or prolene suture as an alternative method for the wound closure. Methods: This prospective study described 30 cases where dermo-traction technique was used for the closure of the wound using infant feeding tube or prolene suture. Study was conducted in Orthopaedics Department of MKCG Medical College, Berhampur from June 2016 to May 2018. Patients requiring skin grafting for their major soft tissue defects or in whom skin grafting or fasciocutaneous flap could not be done were included in study. Results: Out of 30 patients, 2 were lost to follow-up. Average age of study participants was 39.1 years. Male constituted 67.8%. 78.5% of patients had wound in leg, 14.3% in thigh region, rest had on ankle. 82.1% had an open fracture wound, 10.7% had post-operative wound dehiscence and 7.1% soft tissue injury. Average wound healing time was 15.3days with average 5 tightening session of suture. Wounds healed eventually in 26 patients and 2 patients had an infection. Among 26 patients 9 patients had delayed primary and 17 had secondary closure of wound. Conclusions: It can be concluded that gradual closure of the wounds with soft tissue defects can be achieved by applying dermo-traction technique using prolene suture or infant feeding tube with average 15 days of time. So dermo-traction using infant feeding tube or prolene suture is a simple, inexpensive, effective and technically sound alternate solution for closure of wound.